Removal of hexavalent chromium from aqueous solution using canola biomass: Isotherms and kinetics studies - Davoud Balarak; Yousef Mahdavi; Fardin Gharibi; Shahram Sadeghi (Journal of Advances in Environmental Health Research, 2014)
The removing of hexavalent chromium from wastewater or decreasing its chromium (VI) content up to the permitted levels is important due to its non-biodegradation, bioaccumulation, and cancer-causing and toxic effects. In the present study, biosorption of Cr (VI) from aqueous solutions using canola was investigated. The various physicochemical parameters such as pH, initial Cr (VI) ion concentration, adsorbent dose, and equilibrium contact time were optimized in batch adsorption system. The results showed that the optimum amount of each parameter was as follows: initial concentration = 10 mg/l, pH = 3, contact time = 75 minutes, and adsorbent dosage = 5 g/l. The maximum adsorption efficiency was about 99.1%. The maximum adsorption capacity was calculated and was about 10.67 mg/g of adsorbent. Moreover, the sorption data was best fitted on the Langmuir isotherm model and adsorption kinetic is adopted with the pseudo-second-order model. The results of the present study suggest that canola can be used beneficially in treating aqueous solutions containing heavy metal ions.